Mapping of a Novel Quantitative Trait Locus Conferring Bacterial Blight Resistance in the Indigenous Upland Rice Variety ULR207 Using the QTL–Seq Approach - Tanawat Wongsa; Sompong Chankaew; Tidarat Monkham; Meechai Siangliw; Niranjan Baisakh; Jirawat Sanitchon (Plants, 2025)
Bacterial blight (BB) disease is a serious stress that affects up to 80% of rice yield. Utilizing an elite resistant variety was previously thought to be an alternative way to control disease outbreaks. The indigenous upland rice variety ULR207 is a high-potential donor for the BB resistance breeding program. However, the quantitative trait loci (QTLs) associated with bacterial blight resistance in this variety have not yet been discovered. Therefore, QTLs associated with BB resistance need to be identified. In this study, we identified the QTLs associated with BB resistance in the F2:3 population crossed between the BB resistance variety ULR207 and Maled Phai, as well as a susceptible variety, via QTL-seq analysis and bulk-segregant analysis. We found a new QTL-associated BB resistance locus (qBBchr8) mapped on chromosome 8. Five positions were candidates, including Os08g0110700, Os08g0115200, Os08g0131300, Os08g0139500, and Os08g0163900. Afterwards, Kompetitive Allele-Specific PCR (KASP) markers specific to the SNP variant and the position of each gene were designed. These markers, associated with the disease lesion length phenotype, were validated with another 178 individual plants of the F2 population via single-marker analysis. This analysis revealed that the position Os08g0110700 was the strongest locus, with a PVE of 15.00%. The results suggest that this KASP SNP marker could be used to improve elite rice for BB resistance.